f-g=3g

Simple and best practice solution for f-g=3g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f-g=3g equation:


Simplifying
f + -1g = 3g

Solving
f + -1g = 3g

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add 'g' to each side of the equation.
f + -1g + g = 3g + g

Combine like terms: -1g + g = 0
f + 0 = 3g + g
f = 3g + g

Combine like terms: 3g + g = 4g
f = 4g

Simplifying
f = 4g

See similar equations:

| 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 |

Equations solver categories